Which Students are Exposed to Teachers of Color? - Binsted, Kaitlin; Grissom, Jason A. (Peabody journal of education, 2025)
Research finds many benefits of exposure to teachers of Color, especially for students of Color. However, teachers of Color are underrepresented and unevenly distributed resulting in unequal access to these benefits. We descriptively examine the rate at which cohorts of 3rd to 8th grade students in Tennessee are assigned to teachers of different racial/ethnic identities. We also investigate how school-level factors predict exposure to teachers of Color and same-race teachers. We find a sizeable group of students never have a teacher of Color in a tested subject (i.e. English/language arts, math, science, and social studies) from 3rd to 8th grade and large variation in exposure across regions, districts, and schools. While essentially all White students and most Black students have at least one same-race teacher, very few Hispanic and Asian students do. We find evidence that the presence of Black administrators makes exposure to Black teachers more likely. We also find that schools may strategically assign students within schools to increase student matching to same-race teachers, a pattern even more pronounced for Black students in schools with Black administrators.